PENYUSUNAN MEDIA PEMBELAJARAN MISTERY BOX PADA MATA PELAJARAN PERSAMAAN DASAR AKUNTANSI KELAS X SMK PGRI 2 KEDIRI (Prosiding SEMDIKJAR (Seminar Nasional Pendidikan dan Pembelajaran), 2025)
This research aims to develop the Mystery Box learning media for the topic of Basic Accounting Equation in Grade X of SMK PGRI 2 Kediri as an innovative solution to create a more interactive, varied, and enjoyable learning process. Based on the preliminary study, it was found that the teaching process was still dominated by conventional lecture methods without attractive supporting media, resulting in students feeling bored and many not reaching the minimum mastery criteria (KKM). The Mystery Box media was designed as an educational game using simple materials, equipped with content, practice questions, and answer keys. The validation results by media and material experts showed a very high validity level with an average percentage of 95% (very valid), while the results of limited and wider trials indicated positive student responses with an average score of 88.98% (very valid). Moreover, there was a significant improvement in students’ learning outcomes, where prior to using the media most students’ scores were below the KKM, whereas after learning with the Mystery Box, all students achieved or exceeded the KKM. These findings prove that the Mystery Box media is valid, practical, and effective as an alternative for accounting learning, capable of increasing students’ learning motivation, fostering independence, and encouraging an active classroom atmosphere. It is expected that these findings will serve as a reference for teachers and future researchers to develop similar media with broader material coverage or in digital form.